GAYA KEPEMIMPINAN, DISIPLIN KERJA, DAN KINERJA PEGAWAI - Sri Sulastri Manalu; Muhamad Husni Thamrin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The leadership style applied by leaders to influence their subordinates has a crucial role in determining organizational success. High work discipline will also make it easier for the organization to achieve its goals. This research aims to determine and analyze the influence of leadership style and work discipline on the performance of Dairi Regency Population and Civil Registration Service employees. At the Dairi Regency Population and Civil Registration Service, several problems were encountered, namely performance that was not optimal, the role of leaders, and employee work discipline that was not optimal. This research aims to analyze the significance of the influence of leadership style and work discipline on employee performance at the Population and Civil Registration Service of Dairi Regency. The research method used is descriptive research with a quantitative approach. The population used in this research were all employees at the Dairi Regency Population and Civil Registration Service, totaling 40 respondents with the sampling technique being saturated sampling with a population size equal to the sample size. The data analysis technique used is multiple regression analysis and hypothesis testing (T Test and F Test) with the help of the SPSS 25 program. The results of this research show that leadership style and work discipline have a positive and simultaneous effect on the performance of Dairi Regency Population and Civil Registration Service employees.